Trying to keep alive a non-traumatizing memory of the deceased: A meta-synthesis on the interpretation of loss in suicide-bereaved family members, their coping strategies and the effects on them - Zavrou, Rafailia; Charalambous, Andreas; Papastavrou, Evridiki; Koutrouba, Anna; Karanikola, Maria (My University, 2023)
WHAT IS KNOWN ON THE SUBJECT?: Losing a family member due to suicide has been described as a traumatic experience, as suicide-bereaved relatives grapple to accept the particular character of death and the core elements of guilt, self-criticism and stigma it inflicts. There are long-term consequences for those who bereave due to the suicide of their beloved on, a high risk for mental and physical health problems included. Feelings of guilt and self-stigma influence help-seeking behaviour among suicide-bereaved individuals. WHAT THE PAPER ADDS TO EXISTING KNOWLEDGE?: Coping mechanisms adopted by suicide-bereaved individuals mediate the impact of suicide on their family, and especially on the quality of relationships among them. Supporting others in need can help alleviate guilt and self-blame for the suicide while it enables the bereaved to fulfil their need to keep a non-traumatizing, or even positive bond with the deceased. WHAT THE IMPLICATIONS FOR PRACTICE ARE?: Nursing interventions to facilitate suicide-bereaved family members' participation in self-help support groups and promote their engagement in supporting others in need are important. Mental health nurses need to facilitate the replacement of dysfunctional coping strategies, such as substance use or self-blame with more adaptive ones focused on the personal needs of the bereaved, in order to help them embrace a non-traumatizing memory of the deceased while being in peace with the social environment. Screening for mental health problems and management of shame, self-stigma and guilt during the grieving period needs to be a priority in nursing interventions.
Keywords: carers/families; coping; family members; grief; lived experience; loss and grief; meta-synthesis; suicide; suicide bereavement